Logistics tracking system based on decentralized IoT and blockchain platform - Marouane El Midaoui; El Mehdi Ben Laoula; Mohammed Qbadou; Khalifa Mansouri (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Most of supply chain networks have encountered difficulties when trying to integrate all components and stakeholders (Customers, warehouse, transportation, and raw material production. Etc...), which make supply chain management system suffering from a lack of efficiency and transparency that make a steady increase in good’s falsification and consumer’s disappointment. All information about good’s production, storage and transportation should flow clearly during all stages of the supply chain by tracking and authenticating to avoid product’s contamination or fraud in the network. Current tracking IoT-based systems are built on top of centralized architecture and this leaves a gap for tampering and false information especially in urban area, but also the exsiting solutions cannot allow the information to be shared with authority or consumers. To effectively assess and assure traceability and transparency this paper propose an approach using a distributed ledger (blockchain) besides a configuable IoT-based system to take into account all needed data including specific case of urban area, with an opendata platform at the disposal of stockholders, authority and consumers.